Two stage nasolabial flap for unilateral nasal ala and soft triangle reconstruction - Krittika Aggarwal; Kuldeep Singh; Bikramjit Singh (Turkish Journal of Plastic Surgery, 2021)
Introduction: Nose is the most noticeable feature in the facial profile. Any deformity of nose causes social embarrassment and ridicule. Isolated nasal alar hypoplasia/cleft or traumatic loss is a rare anomaly which requires reconstruction. Congenital deficiency of soft triangle of nose and part of ala is not paid attention to in early childhood. Hence, most of these individuals present in late childhood, adolescence or adulthood. We report ten such cases and their reconstruction using two stage ipsilateral interpolated nasolabial flap. Material and Methods: Demographic data including age, sex, associated co-morbidities, previous surgeries or history of trauma were documented. Patients were in age group of 10-25 years. The mean size of defect was 1.5 X 1.6 cm. Inferiorly based skin flap raised from ala was turned down and used as inner lining. Conchal cartilage graft was placed for support in the first stage itself. Nasolabial flap was raised by subcutaneous dissection and insetting done to create outer cover. Second stage for pedicle detachement was done after 3 weeks. Results: Post operative period was uneventful in all cases. Minimal cosmetic morbidity was noted. Scar was well concealed in the nasolabial crease and colour match was also acceptable with good patient satisfaction at 6-12 months. Conclusion: Nasal alar hypoplasia/cleft, congenital or traumatic, is a rare entity which needs to be recognised and reconstructed. According to the size of the defect, it can be reconstructed with composite cartilage graft or local flaps. Interpolated nasolabial flap with cartilage graft is a good option with minimal scar and excellent patient satisfaction.